KETERLAMBATAN BERBICARA PADA ANAK USIA 5-6 TAHUN - sirjon, sirjon (Jurnal Panrita, 2021)
The purpose of this study was to find out what factors caused speech delays in group B children at Pembina Sentani Kindergarten, Jayapura Regency. This research is a case study research with the research subject found 5 children, consisting of 4 boys and 1 girl. Methods of data collection using interviews and documentation. Based on the results of the study, it can be said that the delay in speaking in group B children in TK Negeri Pembina Sentani Jayapura Regency is caused by a lack of stimulation from parents because they are busy in gardening and selling in the market; the use of regional languages that tend to be dominant; the main residential environment of one region and ethnicity; and a lack of understanding from parents about the importance of speaking in everyday life, especially in supporting children's education in the present and in the future